Atypical extraventricular neurocytoma: A case report - Zhang, Peng; Wu, Cui-Ying; Qin, Jia-Zhen; Xu, Ru-Xiang; Bai, Miao-Chun; Wang, Lu-Ping; Dai, Yi-Wu; Li, Xue-Zhen (Cellular and Molecular Biology, 2020)
Atypical extraventricular neurocytoma (EVN) is a rare condition characterized by diffuse tumor cell hyperplasia, increased neovascularization, increased necrosis, and aggressive characteristics. A case of a 25-year old man who presented with atypical EVN in his left parietal - occipital flaps is reported. Magnetic resonance imaging (MRI) revealed a well-defined globular mass with heterogeneous signals in the left parietal lobe, and mild perilesional edema. After left parietal craniotomy and tumor excision, pathologic examination of the resected tissue revealed that the lesion was localized mainly in the white matter and imbued with tumor cells possessing round hyperchromatic nuclei with perinuclear halos and increased microvascular proliferation. The patient underwent radiotherapy at 21st postoperative day. Over the past 26 months, the patient has been regularly followed up, and so far no neurologic deficits have been observed. The latest MRI showed that the tumor bed was stable with slight peritumoral edema. The results of clinical, histopathological and immunohistochemical examinations indicate that atypical EVN is a rare neoplasm with unique radiographic and pathologic characteristics. It possesses more aggressive properties than typical EVN.